The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s12144-018-9980-x
|View full text |Cite
|
Sign up to set email alerts
|

Are there differences in health professionals’ empathy due to academic and clinical experience?

Abstract: Objective: The health professional's empathy has a positive effect on treatment outcomes and the well-being of both patients and professionals. The aim of this research was to assess the empathy levels of first-year medical and psychology students and to compare these levels with those of trained psychologists and physicians. In addition, we also analysed the potential effects of years of professional practice and the average number of patients treated on the empathy of professionals. Method: We evaluated cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 36 publications
0
17
0
2
Order By: Relevance
“…20 Twenty-one studies had greater participation of female health professionals and/or students. 17,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Regarding the age of the interviewees, Petrucci et al 19 reported the lowest mean (X = 21.27 years; standard deviation [SD] = 3.32) and Charles et al 40 reported the highest (X = 55.91 years; SD = 7.68).…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…20 Twenty-one studies had greater participation of female health professionals and/or students. 17,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Regarding the age of the interviewees, Petrucci et al 19 reported the lowest mean (X = 21.27 years; standard deviation [SD] = 3.32) and Charles et al 40 reported the highest (X = 55.91 years; SD = 7.68).…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…In terms of setting, 10 studies were conducted at hospitals, 19,21,22,30,35,[41][42][43][44][45] 10 were conducted at universities, 18,[23][24][25][26][27][28][29]35,39 two were conducted at both hospitals and universities, 32,38 and the remainder used online surveys. 17,20,31,34,36,37,40 Regarding study design, two types of design were identified among the articles selected: cross-sectional and longitudinal.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
See 3 more Smart Citations